Produção e qualidade de batata-doce em função das doses e parcelamento da adubação potássica - Corrêa, Carla Verônica [UNESP] (2016)
Although there are fertilizer recommendations for comercial cultivation of sweet potato, there are few research papers that relate the effect of potassium fertilizer in top dressing and installment it production and quality. The objective of this work was to evaluate the potassium rates and installment influence in top dressing in sweet potato quality and production. The experiment was lead at São Manuel Experimental Farm and the evaluations at Horticulture Department in São Paulo State University. It was evaluated ten treatments in factorial scheme 3x3+1, with three rates of potassium (60, 90 and 120 kg ha-1 of K2O) in top dressing and three installments (100% planting; 50% (planting) + 50% (top dressing) e 25% (planting) + 75% (top dressing) and one control (without potassium and planting at top dressing). The experimental design was randomized blocks, with four replications. Fresh and dry weight of shoot and commercial roots; number, length and diameter commercials roots, yield, extraction of nutrients per plant and quality post harvest (pH, total acidity, soluble solids, reducing sugars and starch) of commercials roots were evaluated. Linear effect was observed for rates of potassium for all vegetative characteristics in installments 50% (planting) + 50% (coverage) and 25% (planting) + 75% (top dressing). For root production characteristics was observed significant interaction between rates and installment, and the installment 50% (planting) + 50% (top dressing) showed the best results. Yield increased with increasing rates of potassium till 120 kg ha-1 de K2O when installment 50% (planting) + 50% (top dressing). The decreasing order of macronutrient extraction by roots was K> N> Ca> P> S> Mg. Already the decreasing order of the plant extraction was K> N> Ca> Mg> P> S. The potassium rates increased sugars and reduced starch content.